Relationship between Knowledge and Attitude of Employees towards Compliance in Using Personal Protective Equipment (PPE) at PT. Nusantara II Plantation Tanjung Jati Plantation in 2022 - Amelia Putri; Wahyu Syarvina (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
One of the obligations of the PTPN II Tanjung Jati oil palm PKWT Harvesting FFB workers is about knowledge of using Personal Protective Equipment (PPE) for occupational safety and health. From the initial survey conducted by researchers at PT Perkebunan Nusantara II Tanjung Jati, researchers found that several employees had accidents at work due to lack of compliance in using PPE. The purpose of this study was to determine the relationship between knowledge and employee attitudes towards compliance in using personal protective equipment at PTPN II Tanjung Jati. The method used in this study is an analytical survey method using a cross-sectional approach. The population in this study were all employees of PKWT Harvesting Palm Oil FFB at PT. Perkebunan Nusantara II Tanjung Jati, specifically for the harvest section. As of January-March 2022, there are 134 employees. The sample is part of the population of 20 respondents. In this study the sampling technique used is Simple Random Sampling. The conclusion is based on the research above with univariate analysis that more employees do not have good knowledge, negative attitudes and non-compliance, namely most of the respondents have poor knowledge totaling 28 respondents (56.0%), most of the respondents have a negative attitude which amounted to 26 respondents (52.0%), most of the respondents did not comply in using PPE totaling 26 respondents (52.0%). Meanwhile, with bivariate analysis that of 22 respondents who have good knowledge, there are 17 respondents (77.2%) who are obedient to the use of PPE, while out of 28 respondents who have poor knowledge, there are 20 respondents (71.4%) who do not comply with the use of PPE. using PPE and of the 24 respondents who have a positive attitude, there are 17 respondents (70.8%) obedient to the use of PPE, while from 26 respondents who have a negative attitude, there are 19 respondents (72.1%) who do not comply with the use of PPE. It is hoped that the company PT. Perkebunan Nusantara II Tanjung Jati to pay more attention to its employees in the use of PPE in carrying out work activities in order to minimize the incidence of workplace accidents. And more often socialize the use of PPE for the development of knowledge and attitudes so that they are more obedient to the use of personal protective equipment.